183k views
18 votes
62
.
52
=
27
.
39
+
t

User C Bauer
by
5.1k points

1 Answer

9 votes

Answer:

t = 35.13

Explanation:

Simplifying

62.52 = 27.39 + t

Solving

62.52 = 27.39 + t

Solving for variable 't'.

Move all terms containing t to the left, all other terms to the right.

Add '-1t' to each side of the equation.

62.52 + -1t = 27.39 + t + -1t

Combine like terms: t + -1t = 0

62.52 + -1t = 27.39 + 0

62.52 + -1t = 27.39

Add '-62.52' to each side of the equation.

62.52 + -62.52 + -1t = 27.39 + -62.52

Combine like terms: 62.52 + -62.52 = 0.00

0.00 + -1t = 27.39 + -62.52

-1t = 27.39 + -62.52

Combine like terms: 27.39 + -62.52 = -35.13

-1t = -35.13

Divide each side by '-1'.

t = 35.13

Simplifying

t = 35.13

hope it helps !!!!!!!!!!! :)

User Rawand Saeed
by
5.6k points